PROCEDURAL GUARANTEES FOR THE MINOR SUSPECT OR DEFENDANT DETAINED DURING PROSECUTION - Ciurea, Ștefan-Tiberiu (International Journal of Legal and Social Order, 2024)
In the context of current Romanian society, which undergoes an accelerated evolution of the criminal phenomenon generated by the multiplication of youth crimes, the need to ensure a social climate of public safety compelles the judicial bodies to resort to exceptional measures regarding the perpetrators of crimes who are still under the age limit. Within the past few years, not only has the number of such situations increased, but also the typology of crimes committed by youths has undergone changes, going from theft and less serious crimes to rape, drug-related crimes or cybercrimes. This article aims to analyse the procedural guarantees provided by the Romanian criminal law, granted to the minor throughout his legal journey from being the perpetrator of a crime to the legal status of being a suspect/defendant detained by the judicial bodies for the committed felony. Using as research methods documentation, comparative research, analysis of normative acts, doctrinal research and interpretation, the article culminates with a proposal of ferenda law regarding the conditions under which the preventive measure of detention can be taken against a minor suspect/defendant aged between 14-16 years old, who has not yet been subjected to a psychiatric examination, but who has committed a serious crime and his release poses a high risk for society. Finally, the article highlights the importance and effects of respecting the procedural guarantees granted to the detained minor, both from the perspective of exercising the punitive-educational role of the criminal process, and that of restoring the climate of public safety.